2011
DOI: 10.2215/cjn.01720211
|View full text |Cite
|
Sign up to set email alerts
|

Symmetric Dimethylarginine as a Proinflammatory Agent in Chronic Kidney Disease

Abstract: SummaryBackground & objectives Chronic kidney disease (CKD) is characterized by chronic inflammation, considered a nontraditional risk factor for cardiovascular disease, the major cause of death in CKD. Symmetric dimethylarginine (SDMA) was recently demonstrated to induce reactive oxygen species in monocytes. The present study further investigates the inflammatory character of SDMA compared with its structural counterpart asymmetric dimethylarginine (ADMA). Design, setting, participants, & measurementsIn vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
107
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(113 citation statements)
references
References 62 publications
2
107
0
2
Order By: Relevance
“…This is most unlikely to be a ‘false positive’ given first, the P  = 0.013 value. SDMA, unlike ADMA, is only a very weak inhibitor of NO synthase, but it is a substantial mediator of inflammatory change 29. This could not be explained by improved renal function, an important consideration because SDMA is excreted (mainly) unchanged in the urine 30.…”
Section: Discussionmentioning
confidence: 99%
“…This is most unlikely to be a ‘false positive’ given first, the P  = 0.013 value. SDMA, unlike ADMA, is only a very weak inhibitor of NO synthase, but it is a substantial mediator of inflammatory change 29. This could not be explained by improved renal function, an important consideration because SDMA is excreted (mainly) unchanged in the urine 30.…”
Section: Discussionmentioning
confidence: 99%
“…Las mujeres tienen un incremento en la concentración de éste producto mucho más tardío que los hombres y por tanto, éste sería otro factor que podría explicar la disfunción endotelial más severa y precoz en el sexo masculino. La DMAA en enfermedad renal crónica se encuentra en concentraciones altas y recientemente Schepers et al Han descrito un rol porinfl amatorio en ERC, activando NF-κB, lo que lleva al aumento de la expresión de IL-6 y TNF alfa 35 . Todo lo anterior podría contribuir a exacerbar las diferencias de género planteadas.…”
Section: Discussionunclassified
“…Taken together, these findings corroborate to the current concept that SDMA is not an inert compound. Actually, it has been demonstrated that SDMA has pro-oxidant and pro-inflammatory effects, and inhibits nitric oxide production [10,11] . Finally, a recent meta-analysis found that higher levels of ADMA and SDMA were associated with increased risk of all-cause mortality (RR 1.52, 95% CI 1.37-1.68; RR 1.31, 95% CI 1.18-1.46; respectively) and CVD (RR 1.33, 95% CI 1.22-1.45; RR 1.36, 95% CI 1.10-1.68; respectively) [12] .…”
Section: Small Water-soluble Moleculesmentioning
confidence: 99%